Digital Inclusion for Sustainable Prosperity: Bridging the Global North–South Divide (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Digital transformation has become a major driver of global economic growth while creating new challenges in the form of disparities between developed countries (Global North) and developing countries (Global South). This study aims to analyze the role of digital inclusion in bridging these disparities to achieve sustainable prosperity. The research method used is descriptive qualitative with a literature review approach to various international reports and publications from ITU, World Bank, UNDP, and OECD. The results of the analysis show that effective digital inclusion is not only determined by infrastructure development, but also by increased digital literacy, equitable access, and adaptive public policies. Countries that implement comprehensive digital inclusion strategies show significant improvements in economic productivity, access to education, and equitable social welfare. The conclusion of this study confirms that digital inclusion is a strategic instrument in realizing fair, inclusive, and sustainable global development.